Recent Segmental Duplications in the Working Draft Assembly of the Brown Norway Rat - Tuzun, Eray; Bailey, Jeffrey A.; Eichler, Evan E. (Genome Research, 2004)
We assessed the content, structure, and distribution of segmental duplications (≥90% sequence identity, ≥5 kb length) within the published version of the Rattus norvegicus genome assembly (v.3.1). The overall fraction of duplicated sequence within the rat assembly (2.92%) is greater than that of the mouse (1%–1.2%) but significantly less than that of human (∼5%). Duplications were nonuniformly distributed, occurring predominantly as tandem and tightly clustered intrachromosomal duplications. Regions containing extensive interchromosomal duplications were observed, particularly within subtelomeric and pericentromeric regions. We identified 41 discrete genomic regions greater than 1 Mb in size, termed “duplication blocks.” These appear to have been the target of extensive duplication over millions of years of evolution. Gene content within duplicated regions (∼1%) was lower than expected based on the genome representation. Interestingly, sequence contigs lacking chromosome assignment (“the unplaced chromosome”) showed a marked enrichment for segmental duplication (45% of 75.2 Mb), indicating that segmental duplications have been problematic for sequence and assembly of the rat genome. Further targeted efforts are required to resolve the organization and complexity of these regions.
10.1101/gr.1907504